Pengolahan Air Gambut dengan Menggunakan Pengolahan Lengkap di Sungai Putat Kota Pontianak - Syahrul, Gusti; Kadaria, Ulli; Nugrahaeni, Putranty Widha (Jurnal Teknologi Lingkungan Lahan Basah, 2025)
Water used for daily needs must meet the quality of clean water in accordance with applicable laws and regulations. Peat water has high levels of iron (Fe), pH, color and turbidity so that it is not suitable for daily use because it will have a negative impact on health. The purpose of this study was to analyze the quality of peat water after peat water treatment using complete treatment in the Putat River, Pontianak City. The method used is through the process of neutralization, coagulation - flocculation, sedimentation and filtration. Laboratory analysis data from the treatment results showed a decrease in iron (Fe) levels before treatment with an average of 1.6311 mg / L and after treatment with an average of 0.1391 mg / l with a reduction effectiveness of 91.47%. The color before treatment with an average of 570 TCU after treatment with an average of 23 TCU with a reduction effectiveness of 95.96%. The pH before treatment with an average of 4.41 after treatment with an average of 6.82. Turbidity before processing with an average of 19 NTU after processing with an average of 2.5 NTU with a reduction effectiveness of 86.84%. Keywords : Color, Filtration, Iron (Fe),   Peat water, pH dan Turbidity